STABILITY OF A THERMOPHILIC ANAEROBIO DIGESTOR UNDER NON-COMMON OPERATING CONDITIONS - Morales Ch, Edson (2020)
This study investigates the effects of reducing hydraulic retention times, to assess the stability of a thermophilic anaerobic digester (55° C), for treating a sludge produced in a treatment plant wastewater Valladolid, with a composition average COD 35,982 mg / L; SV 18,5 g / L; pH 8,08; N-NH3 347,5 mg / L; N-NKT 1833,8 mg / kg. It was proposed to work modifying the hydraulic retention time progressively reducing from 22,52 to 4,5 days in three stages for a period of 1001 days, increasing the feed flow rate and increasing the values of the organic loading rate. The results showed that the reactor entered into stress processes due to the increase in the reactor load, but they were tolerated and continued generating biogas and the elimination of SV of 37 % on average.